The ANALYSIS OF ETHIOPIAN BASKETBALL PREMIER LEAGUE FOR THE YEAR 2020/21G.C MATCH : ANALYSIS OF ETHIOPIAN BASKETBALL PREMIER LEAGUE FOR THE YEAR 2020/21G.C MATCH - TAGESSE, MULUGETA (INTERNATIONAL JOURNAL OF RESEARCH PEDAGOGY AND TECHNOLOGY IN EDUCATION AND MOVEMENT SCIENCES, 2022)
ABSTRACTThe sport of basketball is deﬁned as “A game played between two teams of ﬁve players in which goals are scored by throwing a ball through a netted hoop ﬁxed at each end of the court (Oxford Dictionaries, 2017). In the country Ethiopia different sport competitions were held every year. The Ethiopian basketball league is one of the competitions held in the country. Basketball game is one of the competitions held in the country with the support of great fun because the game is very interesting and its objective is to shot a ball in the basket with a 24 second shooting attempt interval, in basketball, the shot clock   is a timer designed to increase the game's pace and scoring (databaseBasketball.com entry Archived 2006). But the shooting results of all team are too much small not only the University sport competition but also the basketball clubs of the country. The average score of the Ethiopian basketball club is no more than 60 points per game with in the total time of 40 minutes but they have a minimum chance of 50 attempts in average for a team with in the total time of the game. And it can be increased by the rebounding opportunity of the team. The investigation of this research finding will show the analysis of different variables of basketball competitions like passing accuracy, shooting attempt and shooting accuracy, ball interceptions and rebounding.The population of the study was all basketball clubs which were participate in Ethiopian basketball league competitions which were held at Bahirdar from this population the researcher decided purposively to have a sample size of all 5 male basketball clubs match. The researchers used purposively to have a sample of 5 male basketball teams of 4 matches these are a match between Diredawa kenema basketball club Vs Wolkitie town basketball club, Hawasa town basketball club Vs Yeka Subcity basketball club, Hawasa town basketball club and Wolkitie town basketball club and Gondar town basketball club and Diredawa kenema basketball club to analyse the shooting status, passing status rebounding status and the ball interception status of the clubs per match.Based on the match held at Bahirdar town, clubs shooting accuracy in the first match Diredawa basketball club 036%, Wolkitie basketball club 0.32%, Hawassa basketball club 0.37%, Yeka subcity basketball club 0.30%, and Gonder basketball club 0.33% was recorded  and in the second match Hawassa basketball club 0.35%, Wolkitie basketball club 0.34%, Diredawa basketball club 0.41% was recorded. As shown the percentage of shooting accuracy of all clubs the status is low compared with the minimum attempt of shooting per game.